Geoarqueología en la estepa fueguina, Argentina. Efectos de los procesos geomorfológicos sobre material arqueológico de superficie - Oria, Jimena (2014)
Results from the geoarchaeological analyses carried out at two archaeological localities in the hinterland steppe of Tierra del Fuego (southernmost Argentina), are herein presented. Processes of seasonal running water, mass-wasting and aeolian erosion-accumulation occur over concentration of scarce remains usually recorded at the surface. The two studied cases (the Amalia 5 site and the Duna O´Connor find) come from similar environments of shallow lake surroundings. Each case-study was exposed to different geomorphological processes that altered not only each piece itself but also the integrity and resolution of the archaeological contexts. Wind and water were identified as the main agents acting upon the archaeological remains. The lithic materials were analyzed following several indicators: raw material (lithology and texture), artifact size, percentage of cortex on the lithic surface, degree of fragmentation and surface alteration (polishing and abrasion). Likewise, a detailed description of the geomorphological setting and processes that took place in these sites was done, to identify the possible link between these processes and the characteristics of the archaeological record. The Amalia 5 site is located within a gully excavated on aeolian deposits, some of them edaphized, and overlying finegrain sedimentary rocks and conglomerates. Collectors for sediments were installed, to control dimensions of materials that could be blown by wind. In both localities topographic and stratigraphic profiles were surveyed using Total Station and a differential GPS. In spite of the differences related to the geomorphological and archaeological contexts, the results have shown strong similarities in the use of the raw materials, in the type of artifacts found and in the taphonomic processes that took place over the assemblages. Though both assemblages come from shallow lake environments, they were located in different landforms. The preservation of both contexts shows low variability concerning the degree of abrasion and polishing, depending on the dominant processes in each shallow lake shores (either running water or wind). From the view point of human occupation, the available lithic resources in both localities are different. The local geomorphology and/or the different availability of raw material, allowed to identify different ways in the use of space; whereas the gully of the Amalia 5 site should have been a place where cobbles and pebbles were available for knapping artifacts (demonstrated by the high frequency of recorded items), in the Duna O´Connor the space could have operated as a place to look for animal resources, since lithic raw material was not available.